C-compactness modulo an ideal - M. K. Gupta; T. Noiri (International Journal of Mathematics and Mathematical Sciences)
We investigate the concepts of quasi-H-closed modulo an ideal which generalizes quasi-H-closedness and C-compactness modulo an ideal which simultaneously generalizes C-compactness and compactness modulo an ideal. We obtain a characterization of maximal C-compactness modulo an ideal. Preservation of C-compactness modulo an ideal by functions is also investigated.